Factors Influencing Online Shopping Decisions in the Fashion Industry - Surjono, Welly (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The purpose of this study is to pinpoint the variables that affect consumers' decisions to purchase online for fashion. This study is crucial because it can assist e-commerce businesses better understand consumer behavior and enhance their marketing tactics, which will have a substantial positive impact on the fields of management and information technology. This research employs a mixed-method methodology that combines qualitative interviews with quantitative survey data. Using an online questionnaire, 500 active Indonesian e-commerce users provided quantitative data, and 20 respondents participated in in-depth interviews that yielded qualitative data. While qualitative data were examined thematically, quantitative data were evaluated using Structural Equation Modeling (SEM) with Smart-PLS software. The key conclusions show that customer service responsiveness, product clarity, user reviews, flexible return policies, and platform trust are significant determinants of online purchasing behavior. Competitive pricing and promotional tactics also have a big impact. These results have consequences for e-commerce organizations, who should concentrate on enhancing aspects of trust, the quality of product information, and efficient promotional techniques to draw in and keep customers. The present study suggests that additional investigation is warranted to examine other variables, including the impact of social media and fashion trends on the behavior of online shoppers.